Efficient and Tunable Reflection of Phonon Polaritons at Built‐In Intercalation Interfaces. Issue 26 (17th May 2021) - Wu, Yingjie; Ou, Qingdong; Dong, Shaohua; Hu, Guangwei; Si, Guangyuan; Dai, Zhigao; Qiu, Cheng‐Wei; Fuhrer, Michael S.; Mokkapati, Sudha; Bao, Qiaoliang
Abstract: Phonon polaritons—light coupled to lattice vibrations—in polar van der Waals crystals offer unprecedented opportunities for controlling light at the nanoscale due to their anisotropic and ultralow‐loss propagation. While their analog plasmon polaritons—light coupled to electron oscillations—have long been studied and exhibit interesting reflections at geometrical edges and electronic boundaries, whether phonon polaritons can be reflected by such barriers has been elusive. Here, the effective and tunable reflection of phonon polaritons at embedded interfaces formed in hydrogen‐intercalated α‐MoO3 flakes is elaborated upon. Without breaking geometrical continuity, such intercalation interfaces can reflect phonon polaritons with low losses, yielding the distinct phase changes of −0.8π and −0.3π associated with polariton propagation, high efficiency of 50%, and potential electrical tunability. The results point to a new approach to construct on‐demand polariton reflectors, phase modulators, and retarders, which may be transplanted into building future polaritonic circuits using van der Waals crystals. Abstract : Embedded intercalation nanostructures are constructed in polaritonic α‐MoO3 flakes, serving as efficient and tunable reflectors for phonon polaritons. Reflected phonon polaritons with low losses exhibit propagation‐dependent reflection phase shifts and propagation‐independent reflectance. Both experiment and simulation results confirm that this nontrivial reflection stems from the permittivity discontinuity at the built‐in interfaces, offering potential electrical tunability.